POTENTIAL OF HERBAL MEDICINE IN ASIA FOR ORAL CANDIDIASIS THERAPY: A SYSTEMATIC REVIEW - MEGAWATI, ANI; WAHYUNI, INDAH SUASANI (International Journal of Applied Pharmaceutics, 2021)
The objective of this review was to provide antifungal recommendations for Oral Candidiasis (OC) derived from herbal medicine based on the research results of the last 5 y. This systematic review was conducted according to Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines using the PubMed and Science Direct databases with studies published between 2016 and 2021. The review was conducted on 13 studies, in vitro and clinical trial. A total of 41 species of plants have studied its antifungal effects on Candida albicans. The Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) varied in the range of 0.098 µl/ml to 125 µl/ml for different types of plants and Candida samples, while the mean inhibition zone (ZOI) was 11 mm. The most recommended herbal medicine for the development of antifungal drugs for oral candidiasis therapy were Nigella sativa, Lawsonia inermis, and Zingiber officinale.